2020
DOI: 10.1021/acsanm.0c00768
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Transport Properties of Fluorographene Directly Grown on Silicates for Possible Biosensor Applications

Abstract: Fluorographene (FG) ultrathin films are directly grown on flexible and nonflexible insulating silicate substrates and characterized in terms of their structural and electronic properties. FG is identified as an in-plane heterostructure consisting of sp 2 and sp 3 carbon domains. Solid-state 19 F NMR shows that fluorine is mainly localized in spaces adjacent to sp 2 carbon domains, which can be explained by a more uniform fluorine distribution in the boundaries between small sp 2 and sp 3 domains, rather than b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…[ 91–93 ] Thus, different doping agents or reduction processes need to be done on rGOs to enhance n‐type or p‐type transport. [ 91,94–98 ] For instance, Hwang et al. [ 11 ] showed that thermally reduced graphene oxide (TrGO) can behave as unipolar (p‐ or n‐type) or ambipolar transistor depending on the number of stacked layers on the semiconductor channel.…”
Section: Discussionmentioning
confidence: 99%
“…[ 91–93 ] Thus, different doping agents or reduction processes need to be done on rGOs to enhance n‐type or p‐type transport. [ 91,94–98 ] For instance, Hwang et al. [ 11 ] showed that thermally reduced graphene oxide (TrGO) can behave as unipolar (p‐ or n‐type) or ambipolar transistor depending on the number of stacked layers on the semiconductor channel.…”
Section: Discussionmentioning
confidence: 99%
“…It can be found that despite the explorations of different applications of vdW of 2D materials with TMs, there is limited or no report on their charge carrier and phonon dynamics, where such studies are vital in confirming the potential of such heterostructures in applications. , , In the present study, the fabrication of vdW of bismuth telluride (Bi 2 Te 3 ), a well-known TM, with graphene, fluorographene, and molybdenum disulfide (MoS 2 ) atomic layers via a simple stacking of layers over a few layers of TM is achieved. These three different 2D systems are considered to form heterostructures with the TM and due to the difference in the parent properties of these layers, such as one is a semimetallic 2D system (graphene , ), the second one is a semiconducting defective 2D system (flurographene , ), and the third one is a 2D semiconductor with excitonic carriers (MoS 2 ). These three 2D systems have unique properties, such as, in graphene, the presence of fast electron transfer, reduced surface contamination, high spatial resolution, large surface area, fast response time, wide detection range, and high sensitivity due to their Dirac cone-related states .…”
Section: Introductionmentioning
confidence: 99%
“…Here, the strain-tunable photoresponsivity of such ultrastable FG-MoS 2 (FGMS) photodetectors is theoretically and experimentally demonstrated. The MoS 2 monolayer (MS) is grown over SiO 2 /Si using a chemical vapor deposition technique, while the FG films are grown directly on as-grown MoS 2 films, as reported before (see Supporting Information). Though the chemical stability of such heterostructure-based photodetectors is proven by us, their mechanical robustness was not verified before.…”
Section: Introductionmentioning
confidence: 99%